2x-6-3i=10-3yi

Simple and best practice solution for 2x-6-3i=10-3yi equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-6-3i=10-3yi equation:


Simplifying
2x + -6 + -3i = 10 + -3yi

Reorder the terms:
-6 + -3i + 2x = 10 + -3yi

Solving
-6 + -3i + 2x = 10 + -3iy

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '3iy' to each side of the equation.
-6 + -3i + 3iy + 2x = 10 + -3iy + 3iy

Combine like terms: -3iy + 3iy = 0
-6 + -3i + 3iy + 2x = 10 + 0
-6 + -3i + 3iy + 2x = 10

Add '6' to each side of the equation.
-6 + -3i + 3iy + 6 + 2x = 10 + 6

Reorder the terms:
-6 + 6 + -3i + 3iy + 2x = 10 + 6

Combine like terms: -6 + 6 = 0
0 + -3i + 3iy + 2x = 10 + 6
-3i + 3iy + 2x = 10 + 6

Combine like terms: 10 + 6 = 16
-3i + 3iy + 2x = 16

Add '-2x' to each side of the equation.
-3i + 3iy + 2x + -2x = 16 + -2x

Combine like terms: 2x + -2x = 0
-3i + 3iy + 0 = 16 + -2x
-3i + 3iy = 16 + -2x

Reorder the terms:
-16 + -3i + 3iy + 2x = 16 + -2x + -16 + 2x

Reorder the terms:
-16 + -3i + 3iy + 2x = 16 + -16 + -2x + 2x

Combine like terms: 16 + -16 = 0
-16 + -3i + 3iy + 2x = 0 + -2x + 2x
-16 + -3i + 3iy + 2x = -2x + 2x

Combine like terms: -2x + 2x = 0
-16 + -3i + 3iy + 2x = 0

The solution to this equation could not be determined.

See similar equations:

| -0.5x+7.68=-0.7x+1.68 | | (4x-1)+6i=2+(5y+2)i | | 6r^/12r | | 32+8=52 | | 4x+12-3x+7=x+4 | | y-(-6)=1/3(x-(-2)) | | -0.5+7.68=-0.7x+1.68 | | 4x^2-3x+9=8x+2 | | 4+11x=-26+x | | 5x+8+3x-x+4=6x-3 | | 22+7=30 | | 4.2(4+3x)-4.8=12 | | 3x-1/2= | | -x^4-3=4 | | t^2-5t-50=0 | | t^2+3t-70=0 | | 4(5m-n)+5(n-m+3)= | | 1.3+0.4x=0.5 | | 5x+1=14x+2 | | 6(x+4)+3=6x+2 | | f=5+4x-x^2 | | (1/16)^3/2 | | 2.17-0.14x=5x-3.741 | | 6a+b+4a+b= | | f(x)=5+4x-x^2 | | 9(v+4)-3v=2(3v+4)-9 | | x^3y^2=cos(piy) | | 7x+2=3x+38 | | 2/5x-9=-3/5x-4 | | 5t^3-5t=0 | | 2.5x+2.3=7.9 | | (1/4)x=6 |

Equations solver categories